1963
DOI: 10.1111/j.2042-7158.1963.tb12799.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Stereoisomerism in Muscarinic Activity

Abstract: The muscarinic activities and rates of hydrolysis by acetylcholinesterase of the optical isomers of the acetyl‐α‐ and acetyl‐β‐methylcholines of known configuration have been determined. The results have been correlated and the possible characteristics of muscarinic receptors outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1966
1966
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Because of sustained contraction of the ileum, presumably caused by accumulated endogenous ACh, , 1963;Cocolas & Robinson, 1970). Furthermore, in contrast to untreated ileum, the three compounds investigated produced the same maximum response in DFP-PrBCM-treated tissue ( Table 2).…”
Section: Resultsmentioning
confidence: 84%
“…Because of sustained contraction of the ileum, presumably caused by accumulated endogenous ACh, , 1963;Cocolas & Robinson, 1970). Furthermore, in contrast to untreated ileum, the three compounds investigated produced the same maximum response in DFP-PrBCM-treated tissue ( Table 2).…”
Section: Resultsmentioning
confidence: 84%
“…On the other hand, a well-defined difference between acetylcholine derivatives and alkyl acetates in their interactions with acetylcholinesterase active surface has been found in the present work. In contrast to the interaction with acetyl p-methylcholine (I) [43] the enzyme did not exhibit stereoselectivity in the case of see-butyl acetate (11) which has an asymmetric centre similar to that of compound (I). The enzymic hydrolysis of sec-butyl acetate under the…”
Section: Discussionmentioning
confidence: 93%
“…The structure of this peripheral receptor has been discussed by Beckett, Harper, Clitherow & Lesser (1961), Beckett, Harper & Clitherow (1963), Waser (1961) and Belleau & Puraneft (1963) with particular reference to the activity of muscarine, muscarone and the highly active quaternary salts of 5-dimethylaminomethyl-2-methyl-1,3-dioxolane. Beckett et al (1963) have suggested that muscarinic drugs may interact with the receptor at an anionic site (site 1), and a cationic site (site 2), separated by 3 to 3.5 A, and also at a third site located at a distance of 5 to 7 A from the anionic site. Because of the existence of free rotation about the =C-CH2 bond oxoTremorine can exist in two planar forms, cisoid or transoid.…”
Section: Resultsmentioning
confidence: 99%